Enzyme-powered motility in buoyant organoclay/DNA protocells. Issue 11 (November 2018) - Kumar, B.; Patil, Avinash; Mann, Stephen
Abstract Reconstitution and simulation of cellular motility in microcompartmentalized colloidal objects have important implications for microcapsule-based remote sensing, environmentally induced signalling between artificial cell-like entities and programming spatial migration in synthetic protocell consortia. Here we describe the design and construction of catalase-containing organoclay/DNA semipermeable microcapsules, which in the presence of hydrogen peroxide exhibit enzyme-powered oxygen gas bubble-dependent buoyancy. We determine the optimum conditions for single and/or multiple bubble generation per microcapsule, monitor the protocell velocities and resilience, and use remote magnetic guidance to establish reversible changes in the buoyancy. Co-encapsulation of catalase and glucose oxidase is exploited to establish a spatiotemporal response to antagonistic bubble generation and depletion to produce protocells capable of sustained oscillatory vertical movement. We demonstrate that the motility of the microcapsules can be used for the flotation of macroscopic objects, self-sorting of mixed protocell communities and the delivery of a biocatalyst from an inert to chemically active environment. These results highlight new opportunities to constructing programmable microcompartmentalized colloids with buoyancy-derived motility. Organoclay/DNA semipermeable microcapsules with catalase-powered oxygen gas bubble-dependent buoyancy are prepared and exploited as synthetic protocells capable of programmed motility and sustained oscillatory movement.